2021
DOI: 10.1163/15685381-bja10046
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic and seasonal shifts in movement and habitat selection of the alligator snapping turtle (Macrochelys temminckii)

Abstract: We aimed to discern the seasonal movement patterns, home range sizes, and microhabitat associations of subadult Macrochelys temminckii in a West Tennessee population. Because this population was previously monitored (i.e., telemetry and habitat use) as juveniles after the initial release in 2005, studying the movement ecology and habitat use of the same released cohort 12 years later allows for unique comparisons between hatchling and subadult ecology. We used radio telemetry to collect movement and microhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Vol. 22, Special Issue 12 confiscated adults and captive-reared juveniles and subadults (Hyder et al 2021, Kessler 2020, Moore et al 2014. Our findings indicate the Alligator Snapping Turtle is more of a habitat generalist than previously thought and will use a diversity of both lotic and lentic aquatic habitat types, as long as they provide an abundance of emergent and submerged structures, overhead canopy cover, and suitable water depth profiles.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Vol. 22, Special Issue 12 confiscated adults and captive-reared juveniles and subadults (Hyder et al 2021, Kessler 2020, Moore et al 2014. Our findings indicate the Alligator Snapping Turtle is more of a habitat generalist than previously thought and will use a diversity of both lotic and lentic aquatic habitat types, as long as they provide an abundance of emergent and submerged structures, overhead canopy cover, and suitable water depth profiles.…”
mentioning
confidence: 67%
“…The success of translocations depends on several factors, such as understanding the ecological requirements of the species and eliminating the original cause of the species decline; a well-planned monitoring program to assess success will help researchers collect information to adapt and improve management moving forward (Dodd and Seigel 1991, Fischer and Lindenmayer 2000, Germano and Bishop 2009, Griffith et al 1989). The long-term measure of success for translocations that are designed to augment or supplement existing low-density populations is the production of stable populations with low extinction risk in the future (Bubac et al 2019, Germano and Bishop 2009, Hyder et al 2021). For long-lived species with low population-growth rates, such a goal may take decades of difficult research effort to assess.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spangler et al (2021) used radio telemetry to track hatchling Alligator Snapping Turtles in southeastern Oklahoma, and they found that hatchlings settled in shallow water areas with abundant cover after a short dispersal period. Hyder et al (2021) investigated ontogenetic shifts in habitat use in a juvenile cohort of reintroduced Alligator Snapping Turtles in western Tennessee. Compared to data collected when the juveniles were first released, these turtles were utilizing deeper habitats and had larger home ranges as subadults.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the decline and disappearance of many Alligator Snapping Turtle populations in Oklahoma, a head-start program was established at Tishomingo National Fish Hatchery in 2000 with the goal of restoring populations in rivers and other suitable wetlands where the species has been extirpated and to supplement small populations that are unlikely to persist without intervention. Head-started juvenile turtles produced from the program and similar programs have been released in Oklahoma (Anthony et al 2015, Moore et al 2013), Illinois (Dreslik et al 2017), Louisiana (Dreslik et al 2017, Glorioso et al 2020), and Tennessee (Hyder et al 2021, Ream 2008).…”
Section: Introductionmentioning
confidence: 99%